The Effect of Active Learning in The Flipped Classroom Learning Model on 6th Grade Science Subjects of Elementary School - Fahdiran, Riser; Serevina, Vina; Putra, Alfangni Vembrian Maha (Journal of physics. Conference series, 2022)
Using the flipped classroom as an alternative learning model during this pandemic is considered appropriate because this learning model can combine internal learning in the classroom with distance learning at home and also the main goal of maximizing the achievement of learning activity goals. Therefore, this study aims to design a flipped classroom or inverted classroom learning model to be applied on 6 th grade Science subject of Elementary School. This type of research is a quasi-experimental design with a non-equivalent. Control group using post-test to be analyzed. The results of this study are the e-learning media supporting the flipped classroom approach that is validated with a good level of feasibility for use during a pandemic like now, as well as the results of trials The field shows that the flipped classroom approach with e-learning does not improve learning outcomes compared to the constructivist approach without e-learning when the two approaches use an active learning process, the increase in student learning outcomes in the two approaches is the effect of active learning instruction compared to the order of instructor participation in the learning process